Modulating extraordinary terahertz transmissions in multilayer plasmonic metasurfaces. (5th November 2020) - Banerjee, Sabyasachi; Lok Abhishikth, Naka; Karmakar, Subhajit; Kumar, Deepak; Rane, Shreeya; Goel, Sanket; Azad, Abul K; Roy Chowdhury, Dibakar
Abstract: Manipulations of light–matter interaction via sub-wavelength plasmonic structures have opened up many new research opportunities in photonics from microwave to the visible spectrum, including the relatively underdeveloped but technologically important terahertz regime. Here, we have studied manipulation of terahertz transmission through a bilayer metasurface consisting of a metallic hole array and a complimentary patch array separated by an ultra-thin dielectric spacer. The terahertz transmission spectra through our studied metasurfaces exhibit characteristic resonances due to the surface plasmon induced extraordinary transmission peak. Our study reveals a counterintuitive blue shift of the transmission peak with increasing spacer thickness, which is explained by reduced Coulomb interaction between two plasmonic layers. The measured quality factor exhibits a strong dependence on the spacer thickness, and the maximum quality factor is observed for a spacer thickness of around λ/30, indicating strong electric-field confinement inside the dielectric spacer. These bilayer plasmonic structures will aid in realizing next-generation terahertz plasmonic devices such as ultrasensitive thin-film sensors, modulators, narrow-band filters, and other nonlinear components.